Madrasah As a Transformation of Islamic Education in North Sumatera - Zulkifli Tanjung (Indonesian Journal Education, 2025)
Madrasahs initially evolved from traditional Islamic educational institutions centered on mosques and Islamic boarding schools (pesantren). This study aims to analyze the formation and development of madrasahs within the Indonesian national education system. The method used is a historical analysis, reviewing the pre-independence to post-independence periods, including the implementation of the Joint Decree (SKB) of the Three Ministers and the accompanying curriculum changes. The results show that madrasahs represent a blend of the pesantren model and the modern education system. Government policy strengthens the position of madrasahs by equalizing their status with public schools and developing a school-based curriculum. These findings confirm the strategic role of madrasahs in the national education system and contribute to the development of Islamic education policies that integrate religious values with national education.